Gender Differences in Polychronicity - Szameitat, André J.; Hayati, Moska (Frontiers in Psychology, 2019)
Polychronicity refers to a personal preference to engage in multitasking. In the current study, we investigated whether male and female participants differed in polychronicity. For this, 167 participants filled out an online questionnaire assessing polychronicity in a variety of ways, including the Multitasking Preference Inventory (MPI). Results showed that women were consistently more polychronic than men. We also found that women showed higher self-rated multitasking abilities, reported to spend more time multitasking, and considered multitasking to be more important in everyday life than men. We conclude that in our sample, which mainly consisted of University students in the United Kingdom, polychronicity shows a significant gender difference.